PEMENUHAN HAK BAGI PENYANDANG BUTA WARNA PARSIAL DALAM MEMPEROLEH PEKERJAAN DI KOTA BANDA ACEH (Studi Pasal 4 Ayat 1 (d) UU No.8 Tahun 2016 tentang Disabilitas) - Faqih Ahmad Pulungan; Hasnul Arifin Melayu; Syarifah Rahmatillah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the implementation of Law Number 8 of 2016 concerning Persons with Disabilities in fulfilling the right to work forindividuals with partial color blindness. Although the law adopts a human rights–based approach to disability protection, it does notexplicitly regulate the legal status of partial color blindness as part of sensory disability, resulting in legal uncertainty in employment practices.Using a qualitative socio-legal approach, this research analyzes both normative regulations and empirical data obtained through fieldinterviews with relevant government institutions and affected individuals in Banda Aceh City. The findings reveal inconsistencies in policyinterpretation among government agencies, leading to discriminatory barriers in access to formal employment for persons with partial colorblindness. The absence of clear technical guidelines has positioned this group in a legal “grey area,” limiting their access to affirmativeemployment policies. This study concludes that the fulfillment of the right to work for persons with partial color blindness requires regulatoryharmonization, clearer disability classification, and rights-based policy implementation to ensure legal certainty and non-discrimination.